Glanzmann's thrombasthenia: a rare bleeding disorder in a Nigerian girl - Ezenwosu, Osita U (Afr Health Sci, 2020)
INTRODUCTION: Glanzmann's Thrombasthenia (GT) is a rare autosomal recessive bleeding disorder due to defective platelet membrane glycoprotein GP IIb/IIIa (integrin αIIbβ3). The prevalence is estimated at 1:1,000,000 and it is commonly seen in areas where consanguinity is high. CASE PRESENTATION: The authors report a 12 year old Nigerian girl of Igbo ethnic group, born of non-consanguineous parents, who presented with prolonged heavy menstrual bleeding which started at menarche 3 months earlier, weakness and dizziness. She had a past history of recurrent episodes of prolonged epistaxis, gastrointestinal bleeding and gum bleeding during early childhood. On examination, she was severely pale with a haemic murmur and vaginal bleeding. The initial diagnosis was menorrhagia secondary to bleeding diathesis possibly von Willebrand's Disease. She was on supportive treatment with fresh whole blood, fresh frozen plasma and platelets until diagnosis of GT was made in the USA. Currently, she is on 3 monthly intramuscular Depo-provera with remarkable improvement. CONCLUSION: To the best of our knowledge, this is the first documented report of GT in our environment where consanguinity is rarely practised. Our health facilities require adequate diagnostic and treatment facilities for rare diseases like GT.